Update on the management of acute heart failure. (March 2018) - Rayner-Hartley, Erin; Virani, Sean; Toma, Mustafa
Abstract : Purpose of review: We provide a concise review of recent studies focusing on the management of patients with acute heart failure (AHF). Recent findings: In well designed randomized trials, no mortality benefit has been observed with the use of diuretics, ultrafiltration, inotropes and vasodilators in AHF. Recent trials examining the role of novel inotropes and vasodilators as well as the role of mineralocorticoid receptor antagonists in the AHF population, is reviewed. Summary: The focus of therapy in AHF should be directed towards symptom management. No mortality benefit has been observed despite good quality studies.